2010
DOI: 10.1159/000319543
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Gene Polymorphisms and Risk of Neovascular Age-Related Macular Degeneration in a Chinese Cohort

Abstract: Aims: To evaluate the association between vascular endothelial growth factor (VEGF) gene polymorphism and the risk of neovascular age-related macular degeneration (AMD) in a case-control study in a Chinese cohort. Methods: We genotyped 4 common single-nucleotide polymorphisms (SNPs), namely –460T/C (rs833061), +405C/G (rs2010963), +674C/T (rs1413711) and +936C/T (rs3025039), simultaneously detected 7 tag SNPs (tSNPs) in the VEGF gene, in 159 neovascular AMD patients and 140 age- and sex-matched control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
2
18
1
4
Order By: Relevance
“…These results may be explained by the close genetic linkage (D'=0.99) between the VEGF-C936T polymorphism and a different single nucleotide polymorphism (SNP) of the gene complement factor H (CFH -rs1061170) that has previously been shown to be associated with AMD (15) . The frequencies of the VEGF-C936T SNP and alleles (Table 2) were not found to differ between both groups, corroborating previous data obtained for Caucasian (0.80) (13) and Chinese populations (0.85) (12) . However, a lower frequency of the 936T allele (0.10) was observed compared to previous studies of Austrian (0.16) (16) and Chinese (0.19) populations (17) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results may be explained by the close genetic linkage (D'=0.99) between the VEGF-C936T polymorphism and a different single nucleotide polymorphism (SNP) of the gene complement factor H (CFH -rs1061170) that has previously been shown to be associated with AMD (15) . The frequencies of the VEGF-C936T SNP and alleles (Table 2) were not found to differ between both groups, corroborating previous data obtained for Caucasian (0.80) (13) and Chinese populations (0.85) (12) . However, a lower frequency of the 936T allele (0.10) was observed compared to previous studies of Austrian (0.16) (16) and Chinese (0.19) populations (17) .…”
Section: Discussionsupporting
confidence: 90%
“…The VEGF-C936T polymorphism has been evaluated in three previous studies with conflicting results. No association was reported in two of the previous studies in Chinese (12) and Cau casian (13) populations. However, a different study in a Chinese population (14) re ported an association between VEGF-C936T polymorphism and AMD.…”
Section: Discussionmentioning
confidence: 64%
“…All retrieved articles were examined by reading titles, abstracts, and full texts to check the eligibility for this meta-analysis. After careful screening, nine case-control studies (Churchill et al, 2006;Richardson et al, 2007;Lin et al, 2008;Janik-Papis et al, 2009;Szaflik et al, 2009;Galan et al, 2010;Qu et al, 2011;Almeida et al, 2012;Jiang et al, 2013) with 2427 cases and 2037 controls were finally included in the meta-analysis (Fig. 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Later, some studies had found VEGFA as a risk factor for AMD, 23,45,46 whereas some others did not. [47][48][49] In a GWAS, the VEGFA SNP rs943080 was significantly associated with AMD in European populations (P ¼ 9 3 10 À16 , OR ¼ 0.87 for the minor allele C). 8 In contrast, a borderline association of rs943080-C with AMD was reported in Asians (P ¼ 0.041, OR ¼ 0.91).…”
Section: Discussionmentioning
confidence: 99%